Preference system for guided the selection of improvement type and assessment of soil based on expert opinion with weighted system - Kurniawan T.B.; Usman F.; Omar R.C.; Sanusi K.A. (IOP Publishing Ltd, 2023)
Disasters; Geotechnical engineering; Groundwater; Life cycle; Software design; Software testing; Engineering practices; Evaluation results; Feasible solution; Ground modification; High groundwater table; Preference systems; Software development life cycle; Testing and evaluation; Soils